Deterioro hemodinámico cerebral tras la administración de bicarbonato de sodio en acidosis metabólica grave: reporte de un caso - Ricardo Bañuelos-Huerta; Nancy Gutiérrez-Vega; Socorro Figueroa-Rivera; Maribel García-Cantú; Montserrat Ramírez-Barranco; Wendy Sartillo-Guerra; Eduardo Yahir Aguilar-Lazcano (Critical Care & Emergency Medicine, 2026)
Abstract: Sodium bicarbonate ($\text{NaHCO}_3$) is used in selected scenarios of severe metabolic acidosis; however, its administration may be associated with complex physiological effects, particularly at the cerebral level. The generation of $\text{CO}_2$ following its administration promotes its rapid diffusion across the blood–brain barrier, which may contribute to paradoxical intracellular acidosis, alterations in cerebral vasoreactivity, and increased intracranial pressure. We present the case of a 70-year-old man with septic shock, chronic kidney disease, and severe metabolic acidosis, in whom sodium bicarbonate was administered during initial resuscitation. During his clinical course, non-invasive neuromonitoring using transcranial Doppler demonstrated findings consistent with increased cerebrovascular resistance and impaired cerebral perfusion. Renal replacement therapy was subsequently initiated; follow-up Doppler studies showed partial improvement in hemodynamic parameters. Nevertheless, the patient had an unfavorable clinical course and developed cardiac arrest without return of spontaneous circulation. This case highlights the importance of individualizing the use of sodium bicarbonate, prioritizing treatment of the underlying cause of acidosis, and considering non-invasive neuromonitoring tools such as transcranial Doppler to assess the cerebral impact of therapeutic interventions in critically ill patients.